2010
DOI: 10.1002/cbf.1625
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of antioxidant combination against D‐galactosamine‐induced kidney injury in rats

Abstract: The protective effects of an antioxidant combination in kidney injury induced by the injection of D-galactosamine (D-GaIN) were examined in the present study. Sprague Dawley female rats were used and divided into four groups as follows: (1) animals injected physiological saline solution, intraperitoneally, (2) animals treated with the combination of ascorbic acid (100 mg kg(-1) day(-1)), beta-carotene (15 mg kg(-1) day(-1)), alpha-tocopherol (100 mg kg(-1) day(-1)), and sodium selenate (0.2 mg kg(-1) day(-1)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Catal et al revealed that GPx enzyme activity had increased by the administration of the antioxidant combination consisting of beta carotene, ascorbic acid, α-tocopherol, and sodium selenate in renal damage induced by d -GAL. 72 In our opinion, the significant positive effects of PTX and CAPE on oxidative stress parameters observed in this study are attributed to their antioxidant properties.…”
Section: Discussionmentioning
confidence: 50%
“…Catal et al revealed that GPx enzyme activity had increased by the administration of the antioxidant combination consisting of beta carotene, ascorbic acid, α-tocopherol, and sodium selenate in renal damage induced by d -GAL. 72 In our opinion, the significant positive effects of PTX and CAPE on oxidative stress parameters observed in this study are attributed to their antioxidant properties.…”
Section: Discussionmentioning
confidence: 50%
“…Few studies have examined the effect of experimental d ‐GalN‐induced acute liver failure in different tissues . Consequently, very little information is available on the effects of d ‐GalN on the brain tissues of rats…”
Section: Discussionmentioning
confidence: 99%
“…It causes diffuse hepatic tissue damage and cellular inflammation, which are evident in the histological and biochemical profiles of tissues . Previous studies indicate that acute d ‐GalN liver toxicity results in oxidative damage in kidneys and lungs . d ‐GalN‐induced liver toxicity causes damage to the brain .…”
Section: Introductionmentioning
confidence: 99%
“…Group II was given Vit U (50 mg/kg/day) [ 19 ] by gavage technic for 3 days. Group III was administered GalN (500 mg/kg) [ 23 ] at a single dose intraperitoneally. Group IV was given Vit U 1 h before treatment with GalN.…”
Section: Methodsmentioning
confidence: 99%